Impact of Accounting Information System on Organizational Effectiveness: A Study of Selected Small and Medium Scale enterprises in Woji, Portharcourt - Nwinee, Kpurugbara; Akpos, Yikarebogha Erorogha; Vincent G., Nwiduuduu; Ibinabo, Tams Waroboko (International Journal For Research In Business, Management And Accounting, 2016)
the effectiveness of organizations is a function of a mix of factors including internally and externally disposed factors. While the contributions of factors like human resource have been extensively studied, the input of specific accounting procedures and practices are yet to be explored extensively. This study was therefore aimed at examining the impact of accounting information system on the performance SMEs in Rivers-State. Two research objectives and questions guided the study. The study used management efficiency and cost control to proxy organizational effectiveness. Data was gathered using a five point likert scale questionnaire and was analyzed using the non-parametric kruskawalis test (H). The findings revealed that by supporting rational operational decision, accounting information system enhances management efficiency and cost control. Sequel to the findings, the researchers among others recommended that accounting officers of SMEs should be trained on the uses and skills relevant for AIS application.